Body image is associated with persistence. A study of the role of weight-related stigma - Styk, Wojciech; Wojtowicz, Ewa; Glibowski, Paweł; Iłowiecka, Katarzyna; Jędryszek-Geisler, Aleksanda; Zmorzyński, Szymon (Frontiers in Psychiatry, 2024)
The study replicates a preliminary report from 2019 on the relationship between body image and persistence. Purpose: The aim of our study was to analyze the associations between body image, persistence, and body weight stereotypes. Patients and methods: A total of 750 individuals were recruited for the study. The research was carried out in computer labs. The procedure consisted of psychological questionnaires (Persistence Scale, The Body Esteem Scale, Perceived Weight Stigma Questionnaire, Weight Bias Internalization Scale, Hospital Anxiety and Depression Scale, Formal Characteristics of Behavior – Temperament Inventory, and NEO-PI-R) and The Maze Test (a computer tool). After completing the Simple Maze Test, saliva samples were collected. Next, the subjects proceeded to the laboratory where anthropometric and body composition measurements were taken. The hormone levels (cortisol and dehydroepiandrosterone) in the collected saliva samples were analyzed via ELISA to determine stress. Results: Body image and persistence are related variables. They are associated with the internalization of stereotypes and perceived stigma related to body weight. These associations are differentially shaped according to sex and the regularity of body weight. In women, a stronger association of these variables with body image was observed, while in men, the relationship with body image was weaker, with a stronger association shown by perceived weight-related stigma. In the group of participants with a BMI<18.5, there was no significant association between the internalization of stereotypes and the analyzed variables. This relationship appeared in the group of subjects with a normal body weight and was strongest in the group of participants who were overweight or obese. Perceived weight-related stigma was most strongly associated with body image in the group with BMI<18.5 kg/m2 and with persistence in the group with BMI>25 kg/m2. Conclusion: Body-related stigma affects not only overweight and obese individuals and its mechanisms may be shaped differently.